The Mediating Role of Biomarkers in the Association Between Subjective Aging and Episodic Memory. (30th September 2022) - Stephan, Yannick; Sutin, Angelina R; Luchetti, Martina; Aschwanden, Damaris; Terracciano, Antonio
Abstract: Objectives: Subjective aging, indexed by subjective age and self-perceptions of aging (SPA), is consistently related to cognition in adulthood. The present study examined whether blood biomarkers mediate the longitudinal associations between subjective aging indices and memory. Methods: Data of 5, 369 individuals aged 50–94 years (mean = 66.89 years, SD = 9.22; 60% women) were drawn from the Health and Retirement Study (HRS). Subjective age, SPA, and demographic factors were assessed in 2012/2014. Interleukin-6, C-reactive protein, albumin, cystatin C, N-terminal pro B-type natriuretic peptide (NT-proBNP), fasting glucose, Vitamin D, hemoglobin, red cells distribution width, and epigenetic aging were assessed as part of the HRS Venuous Blood Study in 2016. Memory was measured in 2018. The mediators (except for epigenetic aging, which was assessed in a subsample) were tested simultaneously in models that accounted for demographic covariates. Results: An older subjective age was related to worse memory partially through higher fasting glucose, higher cystatin C, higher NT-proBNP, and accelerated epigenetic aging. Negative SPA was related to worse memory through lower Vitamin D3, higher fasting glucose, higher cystatin C, higher NT-proBNP, and accelerated epigenetic aging. The biomarkers explained between 2% and 10% of subjective age and between 1% and 8% of SPA associations with memory. Additional analysis revealed that biomarkers continued to be significant mediators when physical inactivity and depressive symptoms were included as additional mediators. Conclusion: The present study adds to existing research on the association between subjective aging and memory by providing new evidence on the biological mediators of this association.